Education Compliance Taking Hypertension Medication to Treatment for Residents in RT. 04 RW. 03 Ngerco Village Kediri Regency, East Java - Anis Akhwan Dhafin; Elsa Mahardika Putri; Okky Intan Mawarni; Neni Probosiwi; Nur Fahma Laili; Tsamrotul Ilmi; Achmad Wahdi (Universitas STRADA Indonesia, 2025)
Hypertension is defined as a condition in which a person experiences an increase in blood pressure above normal. Hypertension occurs when the results of systolic blood pressure measurements are ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg. From the prevalence of hypertension of 32.3% do not routinely take medication. This community service activity aims to increase understanding and knowledge of residents in RT. 04 RW. 03 Kel. Ngerco, Kab. Kediri, East Java regarding compliance with taking hypertension medication. The purpose of this Community Service is to increase the knowledge of hypertension sufferers about hypertension and the importance of compliance with taking medication and increase the compliance of hypertension sufferers. The results of the Community Service activity are known to be patient knowledge about hypertension and the importance of compliance with taking medication in RT. 04 RW. 03 Kel. Ngerco. This activity was carried out using the counseling method and question and answer session. based on the results of the counseling, local residents were very enthusiastic in asking questions and understanding the importance of taking hypertension medication regularly.